Modulation of TNF‐α mRNA stability by human antigen R and miR181s in sepsis‐induced immunoparalysis. Issue 2 (22nd December 2014) - Dan, Cao; Jinjun, Bian; Zi‐Chun, Hua; Lin, Ma; Wei, Chen; Xu, Zhang; Ri, Zhou; Shun, Cheng; Wen‐Zhu, Sun; Qing‐Cai, Jiao; Wu, Yin
Abstract Immunoparalysis is an important pathological mechanism in sepsis. However, an effective small molecule therapy is lacking. Here, we show that ouabain, a Na+, K+‐ATPase ligand, can reverse immunoparalysis in vitro, in vivo, and in clinical samples. Notably, the effect of ouabain was critically dependent on TNF‐α expression. However, ouabain had opposing effects on the stability of TNF‐α mRNA: Ouabain triggered miR‐181 transcription, which promoted TNF‐α mRNA degradation and induced immunoparalysis, and ouabain triggered the nuclear export of human antigen R (HuR), which stabilized TNF‐α mRNA and suppressed immuno‐paralysis. Interestingly, because the miR‐181 binding site is located within the HuR binding site in the 3′‐untranslated region of TNF‐α, in ouabain‐treated cells, HuR competed with miR‐181 for binding to TNF‐α mRNA and recruited TNF‐α mRNA to stress granules, thereby stabilizing TNF‐α mRNA and reversing immunoparalysis. Ouabain also induced GM‐CSF and interferon‐γ expression in a HuR‐dependent manner. Hence, the fine‐tuning of TNF‐α mRNA stability by HuR and miR181 plays a crucial role in immunoparalysis, and Na+, K+‐ATPase ligands are promising agents for immunoparalysis therapy.